Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1051/0004-6361/201220895
|View full text |Cite
|
Sign up to set email alerts
|

Analogs of solid nanoparticles as precursors of aromatic hydrocarbons

Abstract: Context. Aromatic =CH and C=C vibrational bands have been observed within shocked interstellar regions, indicating the presence of aromatic emission carriers such as PAHs, which may have been created from adjacent molecular cloud material by interaction with a shock front. Aims. We investigate the evolution of the aromatic =CH and C=C vibrational modes at 3.3 and 6.2 μm wavelength in heated HAC materials, PAHs and mixed PAHs and HACs, respectively, aiming at an explanation of the evolution of carbonaceous dust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 50 publications
(90 reference statements)
1
23
0
Order By: Relevance
“…However, their anharmonic DFT calculations work well for small PAHs in this spectral region, opening the way to predict the spectrum of larger PAHs (and other hydrocarbons). Finally, Gadallah et al (2013) also found that the 3.3 µm and 6.2 µm AIBs are also clearly observed in the spectrum of heated HAC dust.…”
Section: Possible Carriers Of the 33 µM Uie Featurementioning
confidence: 64%
See 1 more Smart Citation
“…However, their anharmonic DFT calculations work well for small PAHs in this spectral region, opening the way to predict the spectrum of larger PAHs (and other hydrocarbons). Finally, Gadallah et al (2013) also found that the 3.3 µm and 6.2 µm AIBs are also clearly observed in the spectrum of heated HAC dust.…”
Section: Possible Carriers Of the 33 µM Uie Featurementioning
confidence: 64%
“…Fullerenes and fullerene-based molecules, such as hydrogenated fullerenes and buckyonions, may explain some astrophysical phenomena, like the intense UV absorption band at 217 nm (e.g., Cataldo & Iglesias-Groth 2009) or the so-called diffuse interstellar bands (DIBs; see e.g., Cox 2011;Iglesias-Groth 2007;García-Hernández & Díaz-Luis 2013;Díaz-Luis et al 2015). Owing to the remarkable stability of fullerenes against intense radiation and ionization, these molecules are good candidates for being widespread in insterstellar/circumstellar media.…”
Section: Introductionmentioning
confidence: 99%
“…. 3.6µm were observed in the ISM and interpreted as a mix of HAC and PAH absorption representing small dust grains (Gadallah et al 2013). The transmission spectrum of the hot Jupiter WASP-12b is almost completely flat.…”
Section: Discussionmentioning
confidence: 95%
“…By number, class A spectra are the most often observed, followed by class B, and a few class C. The evolution among the profiles is primarily linked to differences in the chemical composition of the emitting molecules or particles. Class A are probably the most aromatic ones, and class C display additional features that are attributed to a more aliphatic character, observationnally (Sloan et al 2007;Boersma et al 2008;Keller et al 2008;Acke et al 2010), and experimentally (Pino et al 2008;Carpentier et al 2012;Gadallah et al 2013).…”
Section: Introductionmentioning
confidence: 99%